Clinicopathological Evaluation of Abnormal Uterine Bleeding with Special Reference to Estrogen Receptor (ER), Progesterone Receptor (PR)2 and HER-2 / NEU Status - Satpathy, Tanushree; Satpathy, Binapani; Satpathy, Prasanna Kumar (Annals of Pathology and Laboratory Medicine, 2018)
Background: Abnormal Uterine Bleeding (AUB) may be defined as any variation from normal menstrual cycle including alteration in its regularity, frequency, duration of flow and amount of blood loss. AUB can present as menorrhoea, metrorrhagia, poly menorrhoea and dysfunctional uterine bleeding. The study aimed to found out the various aetiopathological factors responsible for AUB. To correlate clinical presentation with histopathological examination and also to study the hormone receptor markers ER (Estrogen Receptors), PR (Progesterone receptor) and marker of oncogene HER-2/NEU for prognostication. Methods: This study was conducted during the period Sept. 2012 to January 2015 in the Department of Obstetrics and Gynecology in collaboration with Dept. of Pathology, Hi-Tech Medical College, Bhubaneswar. 140 patients of 15-55 yrs of age groups were randomly selected excluding pregnant patients and patients below 15 yrs and above 55 yrs. All patients were subjected to Transvaginal-ultransonography, saline infusion sonography and dilation and curettage (D&C) along with endometrial biopsy. All histopathological samples were stained with Hematoxylin and Eosin stain (H&E stain) and subsequently immunostaining was done for ER, PR and HER-2 / NEU. Result: 37.20% cases of AUB were observed in the age group of 41-45. 0.7% among age group of 51-55 yrs. 64.3% of rural population & 67.2% of patients from lower socio-economic group had AUB. 48.6% cases presented with menorrhagia and 42.9% cases had etiological features of dysfunctional uterine bleeding (DUB), 20% had endometrial polyp and 14 cases out of 140 had endometrial carcinoma. In the present study ER were positive in 84.7% and PR were positive in 76.7%. HER-2/NEU expression in this study showed different histopathological pattern of endometrium in AUB. The present study also showed HER-2/NEU expression in 21.4% cases of different grades of Endometrial Carcinoma and all DUB cases showed negative HER-2 / NEU expression. Conclusion: In this study clinical presentation, use of different diagnostic modalities and histopathological correlation were reviewed. Large number of patients belonged to age group 41-50 yrs. The incidence of AUB was maximum in rural areas and most patients belong to lower socio-economic group. By use of Hormone receptors expression of ER & PR and observing the over expression of HER-2 / NEU the prognosis of endometrial lesions can be assessed for early and proper management.